Simulação numérica de fluxo de águas subterrâneas do aquífero Rio Claro, na região do campus da UNESP - Rio Claro, SP - Nogueira, Guilherme Emidio Horta [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The water management in any area is highly important to the success of many business and also of life and the understanding of your relationship with the environment brings better control to its demand. I.e. hydrogeological studies are needed under better understanding of the behavior of an aquifer, so that its management is done so as not to deplete or harm it. The objective of this work is the numerical modeling in transient regime of a portion of the Rio Claro aquifer formation in order to get answers about its hydrogeological parameters, its main flow direction and also its most sensitive parameters. A literature review and conceptual characterization of the aquifer, combined with field campaigns and monitoring of local water level (NA), enabled the subsequent construction of the mathematical model by finite elements method, using the FEFLOW 6.1 ® computational algorithm. The study site includes the campus of UNESP and residential and industrial areas of Rio Claro city. Its area of 9.73 km ² was divided into 318040 triangular elements spread over six layers, totaling a volume of 0.25 km³. The local topography and geological contacts were obtained from previous geological and geophysical studies as well as profiles of campus wells and SIAGAS / CPRM system. The seven monitoring wells on campus were set up as observation points for calibration and checking of the simulation results. Sampling and characterization of Rio Claro sandstones shows up a high hydrological and lithological heterogeneity for the aquifer formation. The simulation results indicate values of hydraulic conductivity between 10-6 and 10-4 m / s, getting the Recharge/Rainfall simulation in transient ratio at 13%. Even with the simplifications imposed on the model, it was able to represent the fluctuations of local NA over a year of monitoring. The result was the exit of 3774770 m³ of water and the consequently NA fall. The model is considered representative for the...

A administração das águas em uma área qualquer é de suma importância para o sucesso de muitos empreendimentos e também da vida. A compreensão de seu equilíbrio com o meio é necessária para uma melhor gestão de sua demanda. Logo, estudos hidrogeológicos são necessários no âmbito de melhor entendimento do comportamento de um aquífero, para que sua gestão seja efetuada de maneira a não exaurir ou prejudicar o mesmo. O objetivo deste trabalho é a modelagem numérica hidrogeológica em regime transiente de uma porção do aquífero da Formação Rio Claro no intuito de obter respostas acerca de seus parâmetros hidrogeológicos, suas direções principais de fluxo e ainda seus pontos mais sensíveis a alterações. A revisão bibliográfica e caracterização conceitual do aquífero, aliada a campanhas de campo e de monitoramento do nível d'água (NA) local, possibilitaram a posterior construção do modelo matemático através de elementos finitos, por meio do algoritmo computacional FEFLOW 6.1 ® . O local de estudo inclui o campus da UNESP e áreas residenciais e industriais da cidade de Rio Claro. Sua área de 9,73 km² foi discretizada em 318040 elementos triangulares, distribuídos por seis camadas, totalizando num volume total de 0,25 km³. A topografia do terreno e os contatos geológicos foram obtidos de estudos geológicos e geofísicos anteriores, bem como de perfis de poços do campus e do sistema SIAGAS/CPRM. Os sete poços de monitoramento do campus foram utilizados como pontos de observação para fins de calibração e checagem dos resultados da simulação. Coleta e caracterização de arenitos da Fm. Rio Claro destacam uma alta heterogeneidade litológica e hidrológica para a formação aquífera. Os resultados das simulações apontam para valores de condutividade hidráulica entre 10-6 e 10-4 m/s, ficando a razão Recarga/Precipitação da simulação em regime transiente em 13%. Mesmo com as simplificações...
Keywords: Águas subterrâneas; Aguas subterraneas - Escoamento; Aquiferos; Modelagem geologica; Hidrogeologia; Método dos elementos finitos; Modelos matematicos; Rio Claro (SP)